Gender differences in the responses and attitudes of young adults towards sexual appeals in advertising - Thorne, Sophie (2018)
Sexual appeals are a specific marketing technique which are frequently used in advertising. They are effective in grabbing the consumer’s attention, however previous literature has demonstrated that the successful implementation of sexual appeals depends largely on the target audience and product relevance. If a sexual appeal is not appropriate, it can create negative attitudes towards the advertisement. This ultimately leads to negative associations with the product or brand being promoted.